The Determinants Factors of Womenpreneurship Performances in Low Economic Class : An Evidence from Melaka - Iylia Syafiqah Binti Abdul Malik; Vincent Chan; Cheryl Chan (International Journal of Entrepreneurship, Business, and Creative Economy, 2021)
Within this study, we want to examine factors those determine to the rise of womenpreneurship, since it is one of the most important 2030 Agenda for Sustainable Development to eradicate national poverty as well as to support the innovation and ever-growing economy. The increasing of women's participation in entrepreneurs demonstrated positive impact of female entrepreneurs, not only on the family but also on economic growth and development. We build our theoretical framework based on literature surveys; that factors of an inspiring role model, education on digital skills, and financial support, which taken from Theory of Planned Behaviour (TPB), contribute to this increasing of womenpreneurship participation. As far as we have known, we are among the first who establish the study focused on women entrepreneurs, especially among the B40 economic social class. We employ a quantitative approach of Multiple Regression Linear Analysis with a convenience sample, comprising 100 women entrepreneurs in Melaka. We find that women entrepreneurs with clear targets, would not only possess the right attitude in their entrepreneurial path, but also become the society role models at the same time. Also, when facing the social pressure, womenpreneurs will equip themselves with proper education to grasp more opportunities. Even though limited by the participation rate, especially those in the rural areas, we would like to make recommendations on ways to encourage more women to pursue entrepreneurship, especially during the Covid-19 outbreak.